The duality of the peer effect: the interplay between peer support and peer criminality on offending and substance use during reentry - Mowen, Thomas J. (Crime & delinquency, 2018)
Differential association theory and the closely linked differential coercion/social support theory suggest that peers exert both criminogenic and protective influences on individuals. Yet, little is known about how dimensions of peer criminality and peer support affect reentry outcomes independently and interdependently. Using data from the Serious and Violent Offender Reentry Initiative, mixed-effects models demonstrate that peer criminality relates to significantly higher odds of substance use and criminal offending, whereas peer support relates to significantly lower odds of substance use and offending. Interaction terms between suggest the two exert independent, and not interactive, influences on recidivism. Although peer crime exerts a more robust effect, peer support must be understood as a mechanism that drives desistance independently of peer crime.